THE ROLE OF MATERNAL AND PATERNAL HLA-DRB1* IN CONGENITAL HEART DISEASE OF THEIR CHILDREN - ANDREY V. Shabaldin; ANNA V. Tsepokina; SVETLANA A. Shmulevich; ANASTASIA V. Ponasenko; LYUDMILA N. Igisheva; ELENA V. Shabaldina; OLGA V. Sterzhanova (Фундаментальная и клиническая медицина)
Aim. To study the associations of the maternal and paternal alleles and genotypes within the HLA-DRB1* gene with the risk of congenital heart diseases (CHD) in their children. Materials and Methods. Having performed the genotyping, we compared the allele frequencies and genotypes within the HLA-DRB1* in females (experimental group 1, n = 97) and males (experimental group 2, n = 59) who have children with CHD and in females (control group, n = 54) and males (control group 2, n = 98) with healthy children. Results. HLA-DRB1*03 (OR = 5.56) and HLA-DRB1*11 (OR = 4.31) alleles in females along with HLA-DRB1*07 (OR=2.72) allele and HLA-DRB1*01, 04 (OR=15.81) genotype in males were associated with a high risk of CHD. On the contrary, allele HLA-DRB1*12 (OR = 0.28) and HLA- DRB1*01, 12 genotype (OR = 0.06) in females correlated with a lower CHD risk. Conclusions. Inherited variation within the HLA-DRB1* gene is associated with a high risk of CHD in the next generation.